Model Pembelajaran pada Pelatihan Servis Mesin Katinting - Darmawang; Zulhaji; Faizal Amir (Universitas Negeri Makassar, 2023)
The katinting machine servicing training was held in Rea Village (Bajoe hamlet), Binuang District, Polewali Regency with the aim of providing participants with the skills and knowledge needed in repairing katinting engines in an effective and practical way so that fishing communities can carry out maintenance and repair symptoms of damage to their katinting engines, especially damage that occurs suddenly such as damage to the fuel system and ignition system. The target audience for this training program are fishing communities, including owners and tenants of katinting engines and have the potential to disseminate knowledge or skills to other fishermen who do not have time to participate in the training. The learning model uses the Observe, Imitate, and Do method approach or the ATM method (Observe, Imitate, Do). The benefits of observing are that participants will understand the problem in depth before moving on to the improvement process, through imitation of corrective steps, participants will have concrete examples of how improvements should be made, which facilitate their understanding and reduce errors in implementation, and by carrying out “Direct Experience” participants can apply their knowledge and skills in real situations. This will increase their confidence in facing technical challenges. Overall, training using the ATM method provides significant benefits for participants, because they have the skills needed to repair the katinting engine more efficiently and effectively. The observation and imitation process will help accelerate learning, while the